Vivienne Westwood : The Journey to Establishing and Communicating Brand Value - Jakubovszkaja, Daria (2025)
This bachelor thesis investigates how Vivienne Westwood communicates and rein-forces brand value in the digital era by analysing five years (2018-2023) of Instagram and Facebook activity. Drawing on cultural-branding and value-co-creation theory, the study employs qualitative content, thematic and sentiment analysis, supported by engagement metrics, to decode posts and their audience reactions.